Evaluation of Scalp Hydration and pH Values in Hijab-Wearing and Non-Hijab-Wearing Women - Hidayah RMN; Widjaya MRH; Gunawan H; Sutedja E; Dwiyana RF; Sutedja EK (Dove Medical Press, 2023)
Risa Miliawati Nurul Hidayah, Muhamad Radyn Haryadi Widjaya, Hendra Gunawan, Endang Sutedja, Reiva Farah Dwiyana, Eva Krishna Sutedja Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, IndonesiaCorrespondence: Risa Miliawati Nurul Hidayah, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Tel +62 8122324231, Email risa.miliawati@unpad.ac.idIntroduction: Indonesia is the most populous Muslim-majority country, where some women wear hijab covering their scalp and neck. Some hijab-wearing women complain of scalp problems eg, itch, dandruff, and hair loss, which might be related to severe and chronic skin barrier impairment due to occlusion. Excessive water accumulation in the occluded stratum corneum might result in increased permeability, followed by increased skin pH values. This study aimed to evaluate scalp hydration and pH values in hijab-wearing and non-hijab-wearing women.Material and Methods: This was a cross-sectional comparative analytical study using stratified random sampling methods conducted on 63 subjects, who were divided into two groups, consisting of 33 hijab-wearing and 30 non-hijab-wearing women. Both groups underwent physical examination and their medical history recorded. Scalp hydration was measured using a Corneometer (Courage + Khazaka, Koln, Germany), and scalp pH value was measured using a Skin & Scalp pH Tester (Hanna Instruments® HI981037, Rumania). This study was conducted at the Dermatology and Venereology Clinic of Hasan Sadikin General Hospital Bandung.Results: The mean scalp hydration and pH values were 18.34 ± 2.91 AU and 4.93 ± 0.17, respectively, in hijab-wearing women. Meanwhile, the mean scalp hydration and pH values were 17.71 ± 3.35 AU and 4.91 ± 0.16, respectively, in non-hijab-wearing women. The difference of scalp hydration and pH values between the groups was not statistically significant based on the independent t-test, with p-values of 0.430 and 0.597, respectively.Conclusion: Scalp hydration and pH values in hijab-wearing and non-hijab-wearing women did not differ significantly. Hijab-wearing women should not worry about scalp barrier impairment as long as they do not have any history of underlying scalp and skin disorders, and do not wear hijab in wet condition.Keywords: hijab, hydration, pH, scalp, women